2015
DOI: 10.11648/j.cmr.20150406.13
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors, Clinical Pattern and Outcome of Stroke in a Referral Hospital, Northwest Ethiopia

Abstract: Stroke is one of the commonest causes of morbidity and mortality among non-communicable diseases. Its occurrence has been significantly increasing in Sub Saharan Africa in the last couple of decades. Mortality has been shown to be higher in this area compared to developed countries. Yet, there is a big information gap about stroke in Ethiopia. This study aimed at describing the clinical pattern, risk factors and outcome of adult stroke patients admitted to university of Gondar hospital. Retrospective chart rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
24
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 24 publications
9
24
3
Order By: Relevance
“…Ischemic stroke (48, 65.8%) was the most prevalent type of stroke in this study, which is lower than a study done in Northwest Ethiopia (69.4%) [11]. On the contrary, similar study done at St. Paul's Teaching Hospital showed hemorrhagic stroke was the most common type of stroke accounting for 61.3% of cases with majority of patients being in the 56–70 years age group [9].…”
Section: Discussioncontrasting
confidence: 67%
“…Ischemic stroke (48, 65.8%) was the most prevalent type of stroke in this study, which is lower than a study done in Northwest Ethiopia (69.4%) [11]. On the contrary, similar study done at St. Paul's Teaching Hospital showed hemorrhagic stroke was the most common type of stroke accounting for 61.3% of cases with majority of patients being in the 56–70 years age group [9].…”
Section: Discussioncontrasting
confidence: 67%
“…patients. [12][13][14] From our study, the modifiable risk factors which were recorded are hypertension, cardio vascular disorder, Diabetes Mellitus, Dyslipidaemia and Life style related were Smoking, Alcohol consumption, Obesity which was comparable to the study conducted by MS Jahirul hoque choudhary et al (2015) [15][16][17][18] . From our study, one male Pediatric case was recorded.…”
Section: Discussionsupporting
confidence: 86%
“…In Ethiopia, ischemic stroke has been identified as the sixth leading cause of death [8]. There are only few studies [9, 10] that assessed stroke outcomes in Ethiopia. These studies reported that the incidence of ischemic stroke is more common than hemorrhagic stroke and reported the overall mortality associated with stroke.…”
Section: Introductionmentioning
confidence: 99%